Freeport-McMoRan Copper & Gold, Inc.: An Innovative Voluntary Code of Conduct to Protect Human Rights, Create Employment Opportunities, and Economic Development of the Indigenous People - Sethi, S. Prakash 1934-; Lowry, David B.; Veral, Emre A.; Shapiro, H. Jack; Emelianova, Olga (2011)
Environmental degradation and extractive industry are inextricably linked, and the industry’s adverse impact on air, water, and ground resources has been exacerbated with increased demand for raw materials and their location in some of the more environmentally fragile areas of the world. Historically, companies have managed to control calls for regulation and improved, i.e., more expensive, mining technologies by (a) their importance in economic growth and job creation or (b) through adroit use of their economic power and bargaining leverage against weak national governments, regional and international regulatory bodies. More recently, the industry has had to contend with another set of challenges that involved treatment of indigenous people and their traditional land rights, fair treatment of workers, human rights abuses, and bribery and corruption involving local officials and political leaders. These challenges currently fall outside the traditional areas of regulation and control. Nevertheless, they pose serious threat to the industry’s business practices because of their global scope, threat to company’s reputation, and long-term risks of political instability leading to increasing cost of capital. Industry has responded to these challenges by creating voluntary codes of conduct that would signify their intent to comply with higher standards of conduct, and assuage public opinion that no further action is called for. These codes, however, lack any monitoring mechanism and reporting integrity to assure the public that the industry members are indeed meeting their commitments. Consequently, pressure on the industry continues unabated and with ever increasing calls for mandatory regulation and oversight. This article examines the activities of one mining company, Freeport-McMoRan Copper & Gold, Inc., which has taken a radically different approach in responding to these challenges at its mining operations in West Papua, Indonesia. While cooperating with industry-based efforts of voluntary codes of conduct, Freeport also initiated a radically different response through its own voluntary code that would directly focus on issues of human rights, treatment of indigenous people on whose traditional land its mine was located; economic development and job creation and, improvements in health, education, and housing facilities, to name a few. Additionally, the company earmarked large sums of money and involved representatives of the indigenous people in their management and disbursement. The company took an even more radical action when it committed itself to independent external audits of the company’s compliance with the code, and that these findings and company’s responses would be made public without prior censorship by the company. We analyze the nature of corporate culture, vision and risk-taking propensities of its management that would impel the company to embark on a high risk strategy whose outcomes could not be predicted with any degree of certainty before the fact. The parent company also had to confront discontent among the management ranks at the mine site because of cultural differences and management styles of expatriates and local (Indonesian) managers. Finally, we discuss in some detail the extensive and intensive character of a two phase audit conducted by the outside monitors, their findings, and the process by which they were implemented and reported to general public. We also evaluate the strengths and challenges posed by such audits, their importance to the company’s future, and how such projects might be undertaken by other companies.
Keywords: News Media; Violence; Military; NGO intervention and relationship; third party independent audit and compliance monitoring; top management vision and risk taking propensities; corporate culture values and traditions; Economic Development; Indigenous People; human rights abuses; individual company voluntary code of conduct; industry-wide voluntary codes of conduct; extractive industry; Inc; Freeport-McMoRan Copper & Gold